1981
DOI: 10.1016/s0022-5347(17)54531-0
|View full text |Cite
|
Sign up to set email alerts
|

The Response of Metastatic Adenocarcinoma of the Prostate to Exogenous Testosterone

Abstract: In a retrospective review the response of 67 patient with metastatic adenocarcinoma of the prostate to the administration of exogenous testosterone was analyzed. Among 52 patients in whom objective and/or subjective responses were evaluable 45 experienced unfavorable responses. There was prompt regression of most unfavorable responses with testosterone withdrawal. The duration of treatment required to evoke an unfavorable response was related to the clinical status of the patient. Twenty-five per cent of patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
131
0
9

Year Published

1982
1982
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 227 publications
(142 citation statements)
references
References 7 publications
2
131
0
9
Order By: Relevance
“…Fowler and Whimore, (1981) observed that out of 52 metastatic prostate cancer patients who received ART, 45 exhibited increased cancer progression that could be reversed by androgen withdrawal, whereas 7 experienced symptomatic benefits. Other investigators have observed that in patients with castration-resistant metastatic prostate cancer, ART resulted in either little adverse effect on cancer progression or displayed some biochemical improvement or progression (Mathew, 2008;Morris et al, 2009;Szmulewitz et al, 2009).…”
Section: Art In Prostate Cancer Patientsmentioning
confidence: 99%
“…Fowler and Whimore, (1981) observed that out of 52 metastatic prostate cancer patients who received ART, 45 exhibited increased cancer progression that could be reversed by androgen withdrawal, whereas 7 experienced symptomatic benefits. Other investigators have observed that in patients with castration-resistant metastatic prostate cancer, ART resulted in either little adverse effect on cancer progression or displayed some biochemical improvement or progression (Mathew, 2008;Morris et al, 2009;Szmulewitz et al, 2009).…”
Section: Art In Prostate Cancer Patientsmentioning
confidence: 99%
“…A potential risk of testosterone therapy is an increased incidence of prostate cancer. Whereas androgen depletion hinders the development and clinical progression of prostate cancer, exogenous testosterone may stimulate growth of metastatic prostate cancer [14,15]. Testosterone appears to be an independent predictor of disease and enhances the predictive accuracy for BPH [16].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] More contemporary clinical trials have shown little, if consistent evidence of a carcinogenic influence or the tendency to 'unmask' subclinical prostate cancer when TRT is prescribed to otherwise healthy hypogonadal men. [4][5][6] On the basis of lingering concerns and uncertainly, coupled with the fact that the prostate is known to be a androgensensitive organ, most evidence-based clinical guidelines recommend close surveillance of the prostate with prostate-specific antigen (PSA) and digital rectal examination among men treated with TRT.…”
Section: Introductionmentioning
confidence: 99%